2017
DOI: 10.1177/0021998317692659
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of thermoplastic matrix composites using fused deposition modeling: A comparison of two reinforcements

Abstract: Fused deposition modeling is a fast growing additive manufacturing technology with advantages of low cost, low operation temperature, consistent prototype accuracy, and flexible material change. Fiber-reinforced plastic composite parts have been developed by the fused deposition modeling process to improve the mechanical properties of fused deposition modeling-fabricated pure thermoplastic parts which cannot be used as load-bearing parts in the actual applications. However, porosity found at the fracture inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 28 publications
(37 reference statements)
3
39
1
2
Order By: Relevance
“…The main difference among these properties is based on the direction of the forces. Most of the previous literatures [1,2,10,33,34] normally presented tensile data as a fundamental material property in the design of thermoplastic polymer composites. However, the tensile strength data alone might be insufficient in real applications, since the load is usually derived from a combination of compressive and tensile strengths.…”
Section: Characterisation Of Polyamide Composites 231 Mechanical Pmentioning
confidence: 99%
See 2 more Smart Citations
“…The main difference among these properties is based on the direction of the forces. Most of the previous literatures [1,2,10,33,34] normally presented tensile data as a fundamental material property in the design of thermoplastic polymer composites. However, the tensile strength data alone might be insufficient in real applications, since the load is usually derived from a combination of compressive and tensile strengths.…”
Section: Characterisation Of Polyamide Composites 231 Mechanical Pmentioning
confidence: 99%
“…Therefore, minimising the gaps between the thread lines is crucial to obtain a satisfactory performance of the FDM part. Comparing the mechanical performance between the FDM PA12 and FDM ABS, the majority of studies reported a reduction of strength [1,4,6,21], after incorporated with fillers, albeit at much lower percentages. The improvement in mechanical properties of the FDM parts can typically be observed when the nano-sized fillers or fibres, were incorporated into the polymer matrix system [4,9,42,43].…”
Section: Tensile Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…There are very limited data published for the extrusion nozzle and various feed rates and translational printing speeds are used in other research, therefore, in this study we adopt a print nozzle similar to, but ten times smaller than, those used in short fibre injection moulding [26]. The feed rate of V 1 = 30 mm/s and printing speed of V 2 = 40 mm/s in a similar range as those used in [12,27]. In the current study, the 3D printing is assumed to be processed in a constant high temperature without any solidification.…”
Section: Numerical Studymentioning
confidence: 99%
“…The build platform moves in upward and downward direction and nozzle movement is in 3 dimensional pattern. The continuous reinforcement of any other material into thermoplastic can be done by adding another spool and pass it into the nozzle for printing [2].…”
Section: Introductionmentioning
confidence: 99%